Carbohydrate sources, alanine and calcium for in vitro multiplication of Eucalyptus cloeziana F. Muell. - Lopes da Silva, André Luís; Rech Tormen, Gabriela Cristina; Rondon de Figueiredo, Alexssandra Jéssica; dos Santos Ribeiro, Anatálya; Freire dos Santos, Leandro; Fraga Araújo, Jairton; Ebling Brondani, Gilvano (Iheringia, Série Botânica., 2018)
Eucalyptus cloeziana timber is used for the production of coal and sawmills. The production of elite clones is very efficient via micropropagation, however, this technique must be optimized. Therefore, the aims of this study were to evaluate the presence of different levels of sucrose, glucose, combinations of glucose and sucrose, alanine and calcium on the in vitro multiplication of Eucalyptus cloeziana. Isolated shoots of E. cloeziana were multiplicated under the presence of sucrose and glucose at levels of 0, 15, 30, 45 and 60 g L-1. Sucrose and glucose combinations were tested at levels of 0, 7.5, 15.0, 22.5 and 30.0 g L-1. L-alanine was tested in levels of 0, 20, 40, 80 and 160 mg L-1. Calcium supplementation was carried out with combinations of Ca(NO3)2.4H2O and CaCl2.2H2O at the levels of 556; 1,112; 1,668 and 96; 192; 288 mg L-1, respectively. The percentage of survival, oxidation and callogenesis; shoot number and explant length were evaluated after 30 days of culture. The best level of sucrose was 15 g L-1. The best level of glucose was also 15 g L-1 and it presents reduction in the oxidation of the tissues. Glucose and sucrose combinations did not present suitable results. The presence of L-alanine do not favor the multiplication. The best result for calcium supplementation was found at 1,112 mg L-1 Ca(NO3)2.4H2O and 192 mg L-1 CaCl2.2H2O on solid medium, but the liquid medium avoid the oxidation of the explants.